2017
DOI: 10.1002/brb3.795
|View full text |Cite
|
Sign up to set email alerts
|

Linking kindling to increased glutamate release in the dentate gyrus of the hippocampus through the STXBP5/tomosyn‐1 gene

Abstract: IntroductionIn kindling, repeated electrical stimulation of certain brain areas causes progressive and permanent intensification of epileptiform activity resulting in generalized seizures. We focused on the role(s) of glutamate and a negative regulator of glutamate release, STXBP5/tomosyn‐1, in kindling.MethodsStimulating electrodes were implanted in the amygdala and progression to two successive Racine stage 5 seizures was measured in wild‐type and STXBP5/tomosyn‐1−/− (Tom−/−) animals. Glutamate release measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 71 publications
0
6
1
Order By: Relevance
“…In a previous study, NMDAR2a was co-expressed with NMDAR2b, and both isoforms were significantly increased in kindled rat hippocampus and temporal lobe epilepsy patients ( Mathern et al, 1998 ). Previous work reported a significant increase in glutamate concentration following seizures; however, this significant increase was observed only after chronic exposure to seizure induction, rather than acute exposure like in the current work ( Kolosowska et al, 2016 ; Batten et al, 2017 ). To our knowledge, our study is the first to report changes in hippocampal synaptosome glutamate-related proteins in pregnant mice following acute seizure exposure.…”
Section: Discussioncontrasting
confidence: 59%
“…In a previous study, NMDAR2a was co-expressed with NMDAR2b, and both isoforms were significantly increased in kindled rat hippocampus and temporal lobe epilepsy patients ( Mathern et al, 1998 ). Previous work reported a significant increase in glutamate concentration following seizures; however, this significant increase was observed only after chronic exposure to seizure induction, rather than acute exposure like in the current work ( Kolosowska et al, 2016 ; Batten et al, 2017 ). To our knowledge, our study is the first to report changes in hippocampal synaptosome glutamate-related proteins in pregnant mice following acute seizure exposure.…”
Section: Discussioncontrasting
confidence: 59%
“…Our RNA-seq analyses in control subjects showed that different brain regions had unique transcriptional profiles ( Figure S1). Many of the transcripts enriched in DLPFC were significantly related to synaptic vesicle transport (e.g., KIF5C (12,13), STXBP5L (14)), exocytosis (e.g., STX1A (15)), and neurotransmitter release (e.g,. CADPS2 (16), RIMS3 (17)) (Data file S1).…”
Section: Enrichment Of Differentially Expressed Transcripts Involved mentioning
confidence: 99%
“…For example, it remains unclear whether glutamate that is released from a synapse diffuses to extrasynaptic interstitial fluid, or remains confined in the synaptic cleft due to the rapid action of specific membrane transporters. Transient changes in glutamate extrasynaptic concentrations have been described in the cortex and amygdala using microelectrode biosensors . However, even with the use of highly selective enzymatic biosensors, glutamate spillover from electrically stimulated hippocampal synapses was found to be undetectable .…”
Section: Introductionmentioning
confidence: 99%